Analisis Strategi Penyelesaian Soal pada bagian Prüfungstraining dalam Buku Ajar Netzwerk neu A1 Übungsbuch - Tarisya Aulia Azmi; Hafdarani Hafdarani; Ending Khoerudin (J-EDu Journal - Erfolgreicher Deutschunterricht, 2026)
This study aims to identify and classify task-solving strategies presented in the Prüfungstraining section of the textbook Netzwerk neu A1 Übungsbuch based on Bimmel and Rampillon's (2000) Lernstrategien framework, and to examine their relationship with the A1 Kann-Beschreibungen of the Gemeinsamer Europäischer Referenzrahmen für Sprachen (Common European Framework of Reference for Languages/CEFR). Employing a qualitative descriptive approach with content analysis, the study analyzed instructional statements across the four language skills: listening, reading, speaking, and writing. The findings revealed nine data items of the task-solving strategies, which were classified into three categories: four Direkte Lernstrategien (direct learning strategies), three Indirekte Lernstrategien (indirect learning strategies), and two Sprachgebrauchsstrategien (language use strategies). Six data items were directly aligned with the A1 GER descriptors, whereas three supported learners in completing tasks through monitoring and evaluating the learning process and compensatory communication strategies. These findings indicate that the Prüfungstraining section functions not only as examination preparation but also as a source of strategies for completing tasks in German language learning.